Effect of lockdowns on the epidemiology of pediatric respiratory disease—A retrospective analysis of the 2021 summer epidemic. Issue 4 (2nd February 2023) - Kruizinga, Matthijs D.; Noordzij, Jeroen G.; van Houten, Marlies A.; Wieringa, Jantien; Tramper‐Stranders, Gerdien A.; Hira, Vishal; Bekhof, Jolita; Vet, Nienke J.; Driessen, Gertjan J. A.; van Veen, Mirjam
Abstract: Background: The imposition of lockdowns during the severe acute respiratory syndrome coronavirus‐2 pandemic led to a significant decrease in pediatric care utilization in 2020. After restrictions were loosened, a surge in pediatric respiratory disease was observed in pediatric wards. The aim of this study was to quantify the effect of the lockdown(s) on the incidence of pediatric respiratory disease. Methods: For this multicenter retrospective study, emergency department (ED) visit and admission data between January 2017 and September 2021 was collected from eight general hospitals in the Netherlands. Clinical diagnoses were extracted and categorized in groups ("communicable infectious disease, " "all respiratory infections, " "upper respiratory tract infection, " "lower respiratory tract infection, " and "asthma/preschool wheezing"). The incidence of admissions and ED visits during 2020 and 2021 was compared to the incidence in 2017–2019. Results: Successive lockdowns resulted in a maximum decrease of 61% and 57% in ED visits and admissions, respectively. After loosening restrictions during the summer of 2021, a 48% overall increase in ED visits and 31% overall increase in admission numbers was observed in July compared to the average July in 2017–2019. This was explained by a 381% increase in ED visits and a 528% increase in ward admissions due to overall respiratory infections, mainly due to lower respiratory tract infections. Conclusions: Successive lockdowns in the spring and winter of 2020 and 2021 led to a decreased incidence of communicable infections, especially respiratory tract infections. The resulting lack of pediatric immunity resulted in an off‐season surge in care utilization at an unexpected moment.